Analisis Longitudinal Prevalensi Post-Traumatic Stress Disorder Pengungsi Suriah : Suatu Studi 14 Tahun Pasca Konflik (2011-2025) - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study analyzes the longitudinal trends in the prevalence of Post-Traumatic Stress Disorder (PTSD) among Syrian refugees over a 14-year period (2011–2025) through a systematic meta-analysis of 47 studies, encompassing a total sample of 28,453 refugees. Using a random-effects model, the analysis confirms fluctuating PTSD prevalence, peaking at 83.4% in 2013 (95% CI: 78.2–88.6%) before gradually declining to 42.7% in 2025 (95% CI: 37.3–48.1%). Furthermore, multilevel regression analysis identifies significant predictors, including displacement duration (β = -0.34, p < .001), access to mental health services (β = -0.28, p < .001), and social integration (β = -0.31, p < .001). These findings extend the work of Hassan et al. (2019) on the short-term impact of war trauma and support the resilience model proposed by Mahmoud et al. (2021), highlighting a more complex recovery trajectory. Unlike the previous meta-analysis by Silove et al. (2017), which focused on the first five years of displacement, this study reveals that 37.8% of refugees continue to exhibit chronic PTSD symptoms after 14 years. Notably, key risk factors such as family loss (OR = 2.84, 95% CI: 2.31–3.37) and legal status uncertainty (OR = 2.16, 95% CI: 1.78–2.54) emerge as novel contributions. These findings provide new insights into the long-term trajectory of PTSD among refugee populations and its implications for sustainable mental health interventions.